Hypertension in pediatric kidney transplantation - Seeman, Tomáš; Myette, Robert L; Feber, Janusz (Pediatric transplantation, 2023)
Arterial hypertension (HTN) in children after kidney transplantation is an important risk factor not only for graft loss but also for cardiovascular morbidity and mortality. The prevalence of posttransplant HTN ranges between 60% and 90%. The etiology of posttransplant HTN is multifactorial and includes residual chronic native kidney disease, immunosuppressive therapy, and chronic allograft dysfunction among other causes. Clinic blood pressure (BP) should be measured at each outpatient visit. However, ambulatory blood pressure monitoring (ABPM) is the gold standard method for BP evaluation in children after kidney transplantation, as it often reveals masked and nocturnal HTN; given this, it should be regularly performed in each transplanted child. All classes of antihypertensive drugs are used in the treatment of posttransplant HTN because it has never been proven that one class is better than another. However, in several retrospective studies, the use of calcium channel blockers is associated with better graft function. The optimal target BP for transplanted children is still a matter of debate; it is recommended to target the same BP as for healthy children, that is, <95th percentile. Control of HTN in transplanted children remains poor - only 20%-50% of treated children have normal BP. There is a great potential for improvement of antihypertensive treatment that could potentially result in improvement of both graft and patient survival in children after kidney transplantation.
Keywords: hypertension; Kidney Transplantation; ambulantní monitorování krevního tlaku; retrospektivní studie; Humans; blood pressure; Hypertension; Antihypertensive Agents; transplantace ledvin; chronická renální insuficience; Renal Insufficiency, Chronic; Blood Pressure; left ventricular hypertrophy; transplantation; krevní tlak; antihypertenziva; kidney; Blood Pressure Monitoring, Ambulatory; hypertenze; lidé; dítě; Child; Retrospective Studies